Using Chess As An Instructional Tool: Teachers’ Experiences And Challenges - Chitiyo, George; Zagumny, Lisa (Զանգակ հրատ.)
The integration of chess into education is increasingly recognized for its potential to enhance student learning outcomes and foster critical thinking skills. This study explored the experiences and challenges faced by teachers in implementing chess as an instructional tool across multiple school districts in a southern U.S. state. A survey involving 62 teachers investigated their methods for teaching chess, their perceived impact on their teaching practices, and their influence on students' learning outcomes and classroom experiences. Results revealed that most teachers embraced chess as an engaging and effective pedagogical strategy, noting improvements in students' problem-solving abilities, focus, and engagement. Despite its positive reception, the study also identified challenges related to teachers' limited instructional time, which constrained their ability to fully integrate chess into their curricula. The findings underscore the potential of chess as a transformative educational tool and call for strategic planning to overcome implementation barriers.
Keywords: Pedagogy; Psychology